Literature Review: Peran Kepemimpinan Transformasional dalam Meningkatkan Persepsi Perawat terhadap Handover - febria rizky aulia; Luky Dwiantoro (Jurnal Manajemen Kesehatan Indonesia, 2020)
Nurses' perceptions of the implementation of handovers is various. The wrong perception of the implementation of handovers can affect the communication process that threatens patient satisfaction and safety. The head of space as a transformational leader has an important role in influencing nurses' perceptions in the implementation of handovers. The method used in this paper is study literature from several journal articles. The author analyses and synthesizes to describe the role of transformational leadership in increasing nurses' perceptions of the implementation of the handover from the literature study that has been done, the four elements of transformational leadership have a positive role in influencing factors affecting nurses' perceptions. The more positive the impact of transformational leadership on perception factors, the more will have a positive impact on nurses' perceptions. Through the application of transformational leadership, nurses' perceptions and the quality of handovers can improve. It can be concluded that transformational leadership has a positive role in increasing the perception of nurses. This transformational leadership style can be used as a solution and is highly recommended for use by managers / heads of space as one solution to improve nurses' perceptions